Avaliação da gestão de conhecimento no Centro de Criminalística - Oliveira, Max William Coelho Moreira de (2009)
The present thesis had as objective to analyze the Management of Knowledge at the Center of Criminology of PMERJ. It was intended to verify if the possible actions of Management of Knowledge are tied to the institutional strategy to develop organizational abilities, as well as improving the performance of the Military Experts of the Institution in the accomplishment of the external demands. Therefore, it was searched, at first, to talk about the importance of the management of knowledge for the performance of all the organizations. Right after this, it was exposed the nature of the forensic science service, its peculiar nuances and how the management of the knowledge can contribute to improve the work of the experts. It was considered then to characterize the administration of the CCrim (Centro de Criminalística/Criminology Center) and to identify the positive points and improvement points, about the referring management, searching as methodology the exploratory research, being based on the direct observation (interviews and questionnaires), raising data and information that allowed the diagnosis of cited Center in what it refers itself to the use of the Knowledge (generation, dissemination and filling). As a result, it was concluded that the CCrim has already given meaningful steps in the development of the culture of management of knowledge, but it still has a far way to walk for a well use of it, having as example the absence of one proper structure of an effective System of Management of Knowledge, a system that with practice is not so far from its accomplishment. In addition, the author expected to give to the managers of the Institution instrumental information that can add value to the future initiatives directed to the management of knowledge, being emphasized the effective exploitation of the market of knowledge, suggesting proposals of solution to its resultant problems, and then concluding the work effectively.